REJECTION OF THE POLICY FOR THE RELOCATION OF STREET VENDORS (PKL) IN PADANG PANJANG CITY CENTER MARKET - Ayunda, Defita; Syafrizal, Syafrizal; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This study aims to determine the factors causing the rejection and the form of rejection of the street vendor relocation policy at the Padang Panjang City Central Market. The method used to obtain research results is a descriptive qualitative method. Data collection techniques in this study used in-depth interviews, observation, and documentation. Informants in this study amounted to 9 people with 1 key informant Head of Market Management and 8 street vendors in Pasar Baru Ring Road selected using a purposive sampling technique. The theory used in this study is Ralf Dahrendorf's conflict theory which suggests that there are two groups of interests in conflict, including groups that have authority and groups that must submit to authority. The results of this study indicate that there are two factors causing the refusal of the relocation policy, internal factors and external factors. The internal factors causing the rejection of the relocation policy, are the location of the business that has been occupied for a long time, higher income levels, and lower rents. External factors causing the rejection of the relocation policy, namely the arrangement of trading places that have not been well organized, and inconsistent law enforcement officials in relocating street vendors. The form of rejection of the street vendor relocation policy is in the form of continuing to sell in places that have been banned and protesting.